PENGARUH SUBSTRAT APKIR JAMUR KAYU DAN MACAM BRANGKASAN SUMBER NITROGEN TERHADAP PERTUMBUHAN DAN HASIL JAMUR MERANG (Volvariella volvacea L.) DENGAN SISTEM NAMPAN BERSUSUN - ilvi restiani dewi (AGRONISMA, 2020)
Straw mushroom (Volvariella volvacea L.) has high nutritional value and good prospects for development. The straw mushroom market is still wide, while the supply is still low, it becomes an opportunity to cultivate it. This study aims to determine the response of the growth, yield and economic value (R/C ratio) of straw mushroom by adding wood fungus rejects substrate with different percentage and type of nitrogen source stover using a stacking tray system. This study using a Factorial RCD with two factors. The first factor is the percentage of wood fungus rejects substrate: A0 (control), A1(10% woody rejects substrate), A2 (20% woody rejects substrate), A3 (30% woody rejects substrate) and A4 (40% woody rejects substrate). The second factor is type of nitrogen source stover: N1 (leucaena), N2 (arachis) and N3 (gliricidia). The statistical test used analysis of variance ANOVA and BNJ follow-up level of 5%. The results of this study showed that there was no interaction between the two factors that were tried, but separately the percentage of wood fungus rejects substrates and types of stover had a significant influence on the parameters of observation. Wood mushroom reject substrate 40% gave the best response to almost all parameters of observation. While lamtoro stover gives a better response compared to arachis and gliricidae. The results of farming analysis using. Leucena stover have the highest farming value Rp. 48.004.917,- in 11 planting periods.